FPGA implementation of multi frequency continuous phase frequency shift keying (MCPFSK) modulation techniques for HF data communication - Jaswar, Fitri Dewi; Sha’ameri, Ahmad Zuri (Penerbit Universiti Sains Malaysia, 2004)
In HF (High Frequency) data communication systems [1,2], FSK (Frequency Shift Keying) digital modulation is widely used. The simplicity in the implementation is the main reason for its popularity. Since noncoherent detection is possible, additional components such as timing recovery circuits [3] are not necessary as required in PSK (Phase Shift Keying) modulation.